Increased oxidative metabolism following hypoxia in the type 2 diabetic heart, despite normal hypoxia signalling and metabolic adaptation. - Mansor, L; Mehta, K; Aksentijevic, D; Carr, C; Lund, T; Cole, M; Le Page, L; Sousa Fialho, M; Shattock, M; Aasum, E; Clarke, K; Tyler, D; et al. (Wiley, 2015)
Hypoxia activates the hypoxia-inducible factor (HIF), promoting glycolysis and suppressing mitochondrial respiration. In the type 2 diabetic heart, glycolysis is suppressed whereas fatty acid metabolism is promoted. The diabetic heart experiences chronic hypoxia as a consequence of increased obstructive sleep apnoea and cardiovascular disease. Given the opposing metabolic effects of hypoxia and diabetes, we questioned whether diabetes affects cardiac metabolic adaptation to hypoxia. Control and type 2 diabetic rats were housed for 3 weeks in normoxia or 11% oxygen. Metabolism and function were measured in the isolated perfused heart using radio labelled substrates. Following chronic hypoxia, both control and diabetic hearts upregulated glycolysis, lactate efflux and glycogen content and decreased fatty acid oxidation rates, with similar activation of HIF signallin gpathways .However, hypoxia-induce dchanges were superimposed on diabetic hearts that were metabolically abnormal in normoxia, resulting in glycolytic rates 30% lower, and fatty acid oxidation 36% higher, in hypoxic diabetic hearts than hypoxic controls. Peroxisome proliferator-activated receptor α target proteins were suppressed by hypoxia, but activated by diabetes. Mitochondrial respiration in diabetic hearts was divergently activated following hypoxia compared with controls. These differences in metabolism were associated with decreased contractile recovery of the hypoxic diabetic heart following an acute hypoxic insult. In conclusion, type 2 diabetic hearts retain metabolic flexibility to adapt to hypoxia, with normal HIF signalling pathways. However, they are more dependent on oxidative metabolism following hypoxia due to abnormal normoxic metabolism, which was associated witha functional deficit in response to stress.